Anatomic stem design reduces risk of thin cement mantles in primary hip replacement - Hank, Christian; Schneider, Michael; Achary, Cheryl S.; Smith, Leslie; Breusch, Steffen (Archives of orthopaedic and trauma surgery, 2010)
To analyse the influence of femoral stem design in the lateral plane (anatomic vs. straight) on the cement mantle quality.
Published online: 10 June 2009
Gesehen am 08.03.2023